A 'standard joint'? the role of quantity in predicting cannabis-related problems - Zeisser, C.; Thompson, K.; Stockwell, Tim; Duff, C.; Chow, C.; Vallance, K.; Ivsins, A.; Michelow, W.; Marsh, D.; Lucas, P. (2012)
The 'standard drink' concept is widely used as a standardized measure of alcohol consumption. There is no equivalent measure of cannabis consumption, perhaps due to challenges such as varied joint size, tetrahydrocannabinol content, and means of delivery. This study introduces a new measure of cannabis quantity and examines whether it predicts cannabis-related social problems with and without controlling for frequency of use. Cannabis-related problems, measured by the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), were predicted from cannabis use frequency (days in past month) and quantity (one joint = 0.5g, five bong or pipe hits, 10 puffs), controlling for age and gender. The sample consisted of 665 participants aged 1567 (mean=28.2, SD=11.8) from the British Columbia Alcohol and Other Drug Monitoring Project, High Risk Group Surveys, 2008 to 2009. Cannabis use frequency and quantity were positively associated with cannabis-related problems. Individuals who consumed cannabis daily and consumed more than one joint per day were at the greatest risk of problems. Controlling for frequency, the effect of quantity remained significant for failure to do what is expected due to cannabis use. This study suggests that quantity, above and beyond frequency, is an important predictor of cannabis problems. We discuss the potential usefulness and validity of this new measure in harm reduction.